Demographic Transformation in a Policy Vacuum: The Changing Face of U.S. Metropolitan Society and Challenges for Public Schools. Issue 2 (3rd April 2017) - Mordechay, Kfir; Orfield, Gary
Abstract: Educators and policy makers must confront the race and class disparities in learning opportunities across American society. Nowhere are these disparities more acute than in the country's great metropolitan areas. As the demographic landscape continues to shift, metropolitan areas are fueling the transition to a majority-minority country. This essay provides an overview of the challenges for the country's public schools and offers an alternative path to creating a more just and vital society.